Spatial Liminality as a Framework for Revitalising Dilapidated Abandoned Buildings in Historic Cities: A Case Study - Hamed Tavakoli; Massoomeh Hedayati Marzbali; Mohammad Javad Maghsoodi Tilaki (Land, 2023)
This paper develops the theory of liminality as a guideline for revitalising disused urban fabrics in historic cities. Since Middle Eastern historic cities exist as a transitional phenomenon, spatial liminality is identified as an epistemological tool for their investigation. This paper sets up a mixed-method approach based on questionnaire surveys and field studies in twelve urban blocks in historic Yazd and Kashan. Using an interpretive historical study, it is verified that, during the premodern eras, spatial liminality has been synonymous with the formation of sense of place/citizenship, mainly generated as a result of the existence of in-between spaces in historic cities, which, in turn, could have facilitated the rites of passage for residents. In a quantitative layer, the correlation between dilapidated abandoned buildings (DABs) (i.e., disused urban fabrics) and sense of place/citizenship is investigated in case studies, which unfolds associations that lack of sense of place amongst local communities could convey to the meaning of spatial liminality. The analysis demonstrates DABs are associated with lack of spatial liminality, contributing to the breakdown of sense of community identification/place. Therefore, DABs need to be reutilized while maintaining their heritage values. The discourse identifies in-between spaces that once facilitated spatial liminality and demonstrates a guideline for revitalising historic cities. This study put forward a theoretical contribution that enables the use of spatial liminality to guide the understanding and management of historic cities.